Analisis geostrategi pembangunan ekonomi berlandaskan ideologi bangsa di Kota Malang - Taruna, Virgin Early Hera (Maliki Interdisciplinary Journal, 2025)
The journal aims to analyze economic growth in Malang City, focusing on the application of geostrategy and ideology in improving people's welfare. In addition, the journal provides an analysis of the challenges that need to be faced, such as the lack of ideological awareness. There are several recommendations arising from the conclusion of the information summarized in the journal, which include the development of inclusive public policies, ideological education programs, and collaboration between the government, the community and the private sector to create sustainable economic growth by utilizing a mature geostrategy. This research uses literature research that can be used to answer research problems. The analysis method uses a descriptive approach with data collection techniques from various sources of books and previous journals.